ANTHROPOCENTRIC PARADIGM IS THE NEOBRANCH OF MODERN LINGUISTICS (Conferencea, 2022)
The article explains that the concept of paradigm, their types, anthropocentric paradigm is one of the neo-fields of modern linguistics.